Inaccuracies Analysis of Students' Writings for Inflectional Affixes - Ahmad Sunandar (Indonesian Journal Publisher, 2025)
The primary aim of this research is to identify and analyze the types of inflectional affix errors present in the writings of sixth-semester students majoring in Medical Laboratory Technology at Indonusa Polytechnic Surakarta. The study employs a qualitative method, examining 11 samples of students’ writings to identify, explain, classify, and evaluate the errors. Results reveal that the most frequent error is in the use of plural suffixes (-s/-es), accounting for 59.37 % of total errors, followed by errors in third person singular verbs (-s) 20,31 %, and past tense (-ed) with 6,25 %, then past participle -en/ed with 6,25 %, afterthat progressive –ing 3,12 %. The least common errors involve possessive (-'s) forms with 3,12 % and superlative (-est) with 1,56 %, while no errors were found in comparative (-er) usage or 0 %. The findings highlight the need for more focused grammar instruction, particularly in morphological awareness, to improve students' written accuracy. This study contributes to better understanding of the challenges learners face in mastering English morphology and offers insights for curriculum development and instructional strategies.